FUNGSI DAN KATEGORI KALIMAT SEDERHANA DALAM JURNAL ENGLISH TEACHING FORUM (SUATU ANALISIS SINTAKSIS) - MARDHATILLAH, MARDHATILLAH (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research entitled â€œFunctions and Categories of Simple Sentences in English Teaching Forum Journalâ€ is a syntactic analysis which describes the functions and categories of the immediate constituent in simple sentences. This research is an attempt to identify, classify, and analyze the simple sentences in the Journal in terms of the functions and categories. This is a descriptive study that used the concept of Aarts and Aarts (1982). The function is a linguistic unit that plays its role in a larger linguistic structure and the category is a linguistic unit as something that has individual characteristic. The result of this research shows that, the functions found externally are subject, predicate, and adverbial. Internally, the functions found are predicator and complement which consist of direct object, subject attribute, and predicator complement. The function of indirect object, object benefactive, and object attribute are not found in this journal. The categories found externally are noun phrase, verb phrase, adjective phrase, adverb phrase, and prepositional phrase. Internally, only the structures of the noun phrase which is analyzed. The internal structure of noun phrase found are pre-determiner, post-determiner, pre-modifier, post- modifier and head (H). Keywords: Functions and Categories, Simple Sentence, English Teaching Forum Journal.